THE EFFECT OF DEBT TO EQUITY RATIO (DER) AND NET PROFIT MARGIN (NPM) ON RETURN ON EQUITY (ROE) IN THE PROPERTY AND REAL ESTATE SECTOR AT PT. LIPPO KARAWACI, TBK. PERIOD 2010-2019 - Estu Elkasysyaf; Fitri Astuti (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to investigate the partial effects of Debt to Equity Ratio (DER) and Net Profit Margin (NPM) on Return On Equity (ROE) and their simultaneous effect on ROE in PT. Lippo Karawaci Tbk. Investors must consider various factors, including financial reports, before investing in a company. The study applies a quantitative approach with descriptive and associative analysis of secondary data obtained from the annual reports of PT. Lippo Karawaci Tbk. from 2010 to 2019. The data analysis uses classic assumption tests, descriptive analysis, and SPSS for Windows version 20.0 and Microsoft Excel 2019 to support initial data processing. The study finds that DER has no compelling partial effect on ROE, with a coefficient determination of 21.9%. On the other hand, NPM has a partially substantial impact on ROE, with a coefficient determination of 88.2%. When analyzed simultaneously, DER and NPM significantly affect ROE, with a coefficient determination of 90.8%. This means that 90.8% of ROE in PT. Lippo Karawaci Tbk. can be explained by DER and NPM, while the remaining 9.2% is influenced by other factors not examined in this study.Keywords: Debt to Equity Ratio, Net Profit Margin, and Return On Equity